Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1007/3-540-45441-1_35
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Software Development Effort Based on Use Cases — Experiences from Industry

Abstract: Abstract. Use case models are used in object-oriented analysis for capturing and describing the functional requirements of a system. Several methods for estimating software development effort are based on attributes of a use case model. This paper reports the results of three industrial case studies on the application of a method for effort estimation based on use case points. The aim of this paper is to provide guidance for other organizations that want to improve their estimation process applying use cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0
14

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 9 publications
(10 reference statements)
1
76
0
14
Order By: Relevance
“…Agarwal et al cited by Damodaran and Washington [20] presents an example of use of this method for estimating an Internet project held in Infosys (Bangalore, India). Other experiences of use of UCP in industry were carried out by Anda et al [21], by Ribu [22] and by some companies as the Rational, SUN and IBM [23].…”
Section: B Use Case Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agarwal et al cited by Damodaran and Washington [20] presents an example of use of this method for estimating an Internet project held in Infosys (Bangalore, India). Other experiences of use of UCP in industry were carried out by Anda et al [21], by Ribu [22] and by some companies as the Rational, SUN and IBM [23].…”
Section: B Use Case Pointsmentioning
confidence: 99%
“…Anda et al [21] applied the Karner method [6] in three projects of a software development company in Norway, Sweden and Finland to compare the estimates made by the UCP with the estimates made by senior members of the development projects. The results showed that the estimation performed through UCP method was close to the real estimation performed by experienced developers.…”
Section: B Use Case Pointsmentioning
confidence: 99%
“…In this way, each team can work independently on a particular requirement without waiting for others. To evaluate the efforts of developing a requirement, we refer to [21,22] for techniques based on XML use cases and feature estimations.…”
Section: Introductionmentioning
confidence: 99%
“…An estimation method based on use cases, the use case points method, was introduced by Karner [9]. This estimation method has been evaluated in several software development projects with promising results [2,3,12]; it was considered easy to use and performed similar to or better than teams of very experienced software developers. Nevertheless, more knowledge is needed about how to apply the method and tailor it to a specific organization.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, more knowledge is needed about how to apply the method and tailor it to a specific organization. We evaluated the use case points method on three projects as the first activity in a software process improvement project on improving estimation in a Scandinavian software development company, Mogul [3]. Since then, the company has also applied the method on a couple of other projects with success.…”
Section: Introductionmentioning
confidence: 99%